Integrated requirement of non‐specific and sequence‐specific DNA binding in Myc‐driven transcription. (1st April 2021) - Pellanda, Paola; Dalsass, Mattia; Filipuzzi, Marco; Loffreda, Alessia; Verrecchia, Alessandro; Castillo Cano, Virginia; Thabussot, Hugo; Doni, Mirko; Morelli, Marco J; Soucek, Laura; Kress, Theresia; Mazza, Davide; et al.
Abstract: Eukaryotic transcription factors recognize specific DNA sequence motifs, but are also endowed with generic, non‐specific DNA‐binding activity. How these binding modes are integrated to determine select transcriptional outputs remains unresolved. We addressed this question by site‐directed mutagenesis of the Myc transcription factor. Impairment of non‐specific DNA backbone contacts caused pervasive loss of genome interactions and gene regulation, associated with increased intra‐nuclear mobility of the Myc protein in murine cells. In contrast, a mutant lacking base‐specific contacts retained DNA‐binding and mobility profiles comparable to those of the wild‐type protein, but failed to recognize its consensus binding motif (E‐box) and could not activate Myc‐target genes. Incidentally, this mutant gained weak affinity for an alternative motif, driving aberrant activation of different genes. Altogether, our data show that non‐specific DNA binding is required to engage onto genomic regulatory regions; sequence recognition in turn contributes to transcriptional activation, acting at distinct levels: stabilization and positioning of Myc onto DNA, and—unexpectedly—promotion of its transcriptional activity. Hence, seemingly pervasive genome interaction profiles, as detected by ChIP‐seq, actually encompass diverse DNA‐binding modalities, driving defined, sequence‐dependent transcriptional responses. Synopsis: Eukaryotic transcription factors such as Myc exhibit both sequence‐specific and generic backbone‐dependent DNA binding. Here, sequence‐independent Myc engagement of open gene‐regulatory elements is found as a prerequisite for cognate sequence recognition, which in turn is critical for transcriptional activation. Analysis of Myc mutants bearing substitutions in residues that contact either the DNA phosphodiester backbone (MycRA) or specific bases within the E‐box consensus motif (MycHEA) reveals different contributions of each binding mode to genome recognition and gene‐regulatory profiles. The MycRA mutant exhibits a general loss of genome interactions and transcriptional activity in mouse cells. The MycHEA mutant retains genome association profiles comparable to those of the wild‐type Myc protein, but fails to recognize the E‐box and to activate Myc target genes. MycHEA also gains weak affinity for an alternative motif, driving aberrant activation of genes not normally regulated by Myc. These findings highlight the principle that peak‐calling in ChIP‐seq profiles reflects promiscuous binding modalities, and cannot systematically be equated to productive regulatory interactions. Abstract : Sequence‐independent interaction of transcription factor Myc with the DNA backbone is required for its chromatin association and subsequent site‐specific binding as well as transcriptional activation.